Prevalence of transfusion-transmissible infections in the south of the Lara state, Venezuela - Teodoro Vizcaya-Rpdríguez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Studies performed on blood units allow the detection of transfusion-transmissible infections (TTI) through the presence of the etiological agent or the antibodies generated by the donor's immune system against infectious agents. The objective of the study was to determine the prevalence of any TTI in blood donors who attended the Dr. Egidio Montesinos Hospital in the city El Tocuyo during the years 2010-2017. For these 6440 sera were analyzed by the ELISA test of different biotechnology companies, of which 481 cases were reactive to different infections, which gives 7.47% of prevalence to any TTI. The specific results were stratified by TTI, year, sex and origin of the infected donor, obtaining a seroprevalence of 0.66% for HBsAg, for anti-HBc (5.34%), for HCV (0.17%), for infection by Trypanosoma cruzi (0.42%), for infection by Treponema pallidum (0.61%) and for HIV (0.26%). No reactive case was found for HTLV. The population studied can be considered as high risk to transmit HBV given that in this area of influence high figures of their biomarkers are presented with respect to the average of the region, subregion and country.